Geological and archaeological evidence of El Niño events along the coast of El Oro Province Ecuador: Excavations at La Emerenciana a late Valdivia (ca. 2200 1450 B.C.) Ceremonial Center - John E. Staller (Maskana, 2015)
El Niño is a warming of surface sea temperatures in the eastern Pacific Ocean. Such climatic and oceanographic perturbations have dramatic impacts upon the environment and human adaptation. Multidisciplinary evidence from large-scale excavations at the late Valdivia ceremonial center of La Emerenciana, document repeated site abandonments in coastal El Oro Province related to El Niño events. Initial abandonment is related to an intense or Mega-El Niño dated to ca. 2150 B.C., and associated with fossil beach ridge formation. Reoccupation is dated to 2200 until 1450 B.C. Final abandonment of the ceremonial center is dated to ca. 1450 B.C. and is associated with an earthquake and a short-lived reoccupation. Multidisciplinary evidence from excavation, regional settlement survey and statistical evidence from shellfish frequencies are presented to document if repeated and final site abandonment was related to El Niño or a tsunami induced by tectonic events associated with El Niño. Results indicate widespread environmental degradation and geomorphological changes to the surrounding coastline were related to El Niño, and that it was clearly a factor to cultural development and adaptation. These documents provide evidence of the chronology, the intensities and impacts of ancient El Niño events at La Emerenciana and pre-Columbian occupations in the Arenillas River valley, El Oro Province, Ecuador.